2003
DOI: 10.1515/jpem.2003.16.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary-Adrenal Axis and Interleukin-6 Activity in Children with Head Trauma and Syndrome of Inappropriate Secretion of Antidiuretic Hormone

Abstract: IL-6 secreted during an aseptic inflammatory state, such as sustaining head trauma with SIADH, is quantitatively correlated to AVP, indicating that this cytokine is directly and/or indirectly involved in the pathogenesis of SIADH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Mastorakos et al (68) demonstrated that IL-6 can act as an AVP secretagogue. This effect of IL-6 on hypothalamic AVP secretion also was seen in children after head trauma (69). It is interesting that women respond to exercise-induced stress with the production of higher levels of IL-6, perhaps explaining, in part, the increased risk for EAH in women (66).…”
Section: Pathophysiologymentioning
confidence: 77%
“…Mastorakos et al (68) demonstrated that IL-6 can act as an AVP secretagogue. This effect of IL-6 on hypothalamic AVP secretion also was seen in children after head trauma (69). It is interesting that women respond to exercise-induced stress with the production of higher levels of IL-6, perhaps explaining, in part, the increased risk for EAH in women (66).…”
Section: Pathophysiologymentioning
confidence: 77%
“…The widespread and intensive inflammatory state involving the lungs, the liver, the kidneys, the intestines and the lymphatic ganglia induced to increase production of plasma prostaglandins and renin 9,29,33,34 . High serum levels of interleukin-6 have been detected in visceral leishmaniasis 3,32 and can act as a potent stimulus of the hypothalamicpituitary-adrenal axis and to arginine vasopressin(ADH) release too 14,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory mediators (cytokines, free radicals, amino acids and nitric oxide) and excitatory amino acids (such as N-methyl-D-aspartate) appear to be implicated in secondary brain injury development (24,27,28). Cytokines -in particular interleukin-6 -which stimulate vasopressin secretion, may also be involved in the pathogenesis of the syndrome of inappropriate antidiuretic hormone secretion (SIADH) after TBI (29). As the primary injury is not preventable, medical management should be directed at the mechanisms of secondary injury in order to improve outcome.…”
Section: Pathophysiology Of Tbimentioning
confidence: 99%